Worker: The iteration game or coming out of the eternal return. (3rd July 2016) - Roland, Barbara
Abstract : Originally, Worker was a durational performance that emerged at the end of a contract as a labourer in a retirement home. This performance uses a recording loop of the experience testimony and experiments with a process of iteration within a mimetic re-enactment of the repetitive actions and gestures of the cleaning work. In the absence of any equipment, in the imaginary space of a room whose boundaries and furniture were drawn on the ground, the performance at'vacuum' seeks less to represent than to outgrow what the working experience represents in a synthesis of the past and present time. This performance-research therefore allows an epistemic claim about what the experience of work, in that vast machinery of capitalism based on subjection and exploitation, represents, means and implies within a process of subjectivization, and how a game of iteration could become a cathartic experience. Iteration is the process of a performance that opens and explores the social play, the man's potential alienation in the 'machinic' enslavement and subjection devices of capitalism, and experiences the borders of the representation andmimesis, the coming out of the eternal return over time.